Effect of Task-Based Bilateral Arm Training on Upper Extremity Motor Functions among Rural and Urban Community-Dwelling Stroke Survivors in Nigeria - Olumide Ayoola Olaoye; Marufat Oluyemisi Odetunde; Sunday Adeyemi Adejumobi; Temitayo Mary Efunsanmi; Micheal Adewale Akande (West African Journal of Allied Health Sciences, 2026)
Introduction: One of the leading causes of disability in low- and middle- income countries like Nigeria is stroke. During rehabilitation, occupational therapists employ interventions like bilateral arm training (BAT) for motor recovery among stroke survivors (SSVs). However, evidence of BAT's effectiveness, especially in diverse settings like Nigeria, is inconclusive. This study evaluates task-based BAT intervention on upper extremity functions among rural and urban community-dwelling stroke survivors. Methods: This quasi-experimental study recruited 10 rural and 11 urban community-dwelling SSVs from the OT unit of a Nigerian tertiary healthcare facility using purposive sampling. The task-based BAT intervention, consisting of four tasks, was delivered thrice weekly for 8 weeks. Motor functions were assessed using Fugl-Meyer upper extremity scale (FMA-UE), Upper Extremity Functional Index (UEFI), and Wolf Motor Function test (WFMT) at baseline, 4-weeks, and 8-weeks following intervention. Data was analyzed descriptively and inferentially. Results: FMA-UE and WFMT scores showed significant improvement in both groups post-intervention reflecting enhanced motor function and performance. Specifically, there was a significant increase in WFMT scores at the 8-week mark among SSVs in rural communities (mean difference = 3.00, 95% CI [0.14, 6.14], p = 0.031), indicating the importance of longer rehabilitation periods. The changes in FMA-UE, UEFI, and WFMT between rural and urban community-dwelling SSVs were not statistically different. Conclusion: The task-based BAT intervention was effective in improving upper extremity motor functions among SSVs in rural and urban settings. Tailored and individualized rehabilitation strategies, considering the unique characteristics of diverse community settings, are crucial for optimizing stroke recovery outcomes.